Investigation of mechanical properties of AlSi3Cr alloy - Marialaura Tocci; Annalisa Pola; Lorenzo Montesano; G. Marina La Vecchia; Mattia Merlin; Gian Luca Garagnani (Fracture and Structural Integrity)
In the present paper, microstructural and mechanical properties of an innovative AlSi3Mg alloy were studied. Particularly, the effect of the addition of Cr and Mn on tensile strength and impact toughness was evaluated. In fact, the presence of these elements leads to the formation of an intermetallic phase with a globular or polyhedral morphology. It was therefore investigated the role played by Cr-Mn containing particles in the failure mechanism and the influence of the heat treatment parameters. Moreover, tensile and impact tests were performed on A356 samples in T6 condition, whose results were compared with the performance of the innovative alloy. Considering the static properties, the innovative alloy showed remarkable values of tensile strength, while ductility was improved only after heat treatment optimization. Poor impact toughness values were measured and the microstructural analysis confirmed the presence of coarse intermetallics, acting as crack initiation and propagation particles, on the fracture surfaces.